Battleground Korea the British in Korea - Whiting, Charles (Sutton, 1999)
In 1950, Communist-backed North Korean forces invaded the US-protected South. This book aims to provide an account of the conflict, in particular Britain's involvement. The author's narrative is supported with graphic eyewitness accounts.